Acute Impacts of Different Types of Exercise on Circulating α-Klotho Protein Levels - Iturriaga, Tamara; Yvert, Thomas; Sanchez-Lorente, Isabel M.; Diez-Vega, Ignacio; Fernandez-Elias, Valentin E.; Sanchez-Barroso, Lara; Dominguez-Balmaseda, Diego; Larrosa, Mar; Perez-Ruiz, Margarita; Santiago, Catalina (Frontiers in Physiology, 2021)
Introduction: Elevated plasma α-klotho (αKl) protects against several ageing phenotypes and has been proposed as a biomarker of a good prognosis for different diseases. The beneficial health effects of elevated plasma levels of soluble αKl (SαKl) have been likened to the positive effects of exercise on ageing and chronic disease progression. It has also been established that molecular responses and adaptations differ according to exercise dose. The aim of this study is to compare the acute SαKl response to different exercise interventions, cardiorespiratory, and strength exercise in healthy, physically active men and to examine the behavior of SαKl 72h after acute strength exercise. Methods: In this quasi-experimental study, plasma SαKl was measured before and after a cardiorespiratory exercise session (CR) in 43 men, and strength exercise session (ST) in 39 men. The behavior of SαKl was also examined 24, 48, and 72h after ST. Results: Significant differences (time×group) were detected in SαKl levels (p=0.001; d=0.86) between CR and ST. After the ST intervention, SαKl behavior varied significantly (p=0.009; d=0.663) in that levels dropped between pre- and post-exercises (p=0.025; d=0.756) and were also significantly higher compared to pre ST values at 24h (p=0.033; d=0.717) and at 48h (p=0.015; d=0.827). Conclusions: SαKl levels increased in response to a single bout of cardiorespiratory exercise; while they decreased immediately after strength exercise, levels were elevated after 24h indicating different klotho protein responses to different forms of exercise.